Quality Control and Efficiency of Pants Production Process Using Six Sigma DMAIC and Triz at PT Magnum Attack Indonesia - Ni Putu Sania Sita Devi; Rudi Nurdiansyah (Eduvest - Journal of Universal Studies, 2025)
Manufacturing competition demands improved quality and efficiency with the lowest possible defects. This study optimizes the pants production process at PT Magnum Attack Indonesia through the integration of Six Sigma DMAIC and TRIZ. Secondary data for July–December 2024 were analyzed to map CTQ, calculate DPMO and sigma levels, and identify root causes using Pareto and fishbone; Improvement recommendations are formulated through the TRIZ contradiction matrix and inventive principles. The results showed a total production of 6,951 units with 430 defects (DPU 0.06186; Final Yield 93.82%; total DPMO 127,024; average sigma 4.45). The dominant defects were suture (43.95%) and precision (31.86%) which accounted for 75.81% of the total defects. Key solutions: layout/ergonomics and visual aids (principle 17), enforcement of inspection SOPs (principle 10), local quality in critical embroidery areas (principle 3), and digitization of CAD-based techpacks (principle 28). This approach suppresses defects without sacrificing productivity and provides a basis for continuous improvement for increased competitiveness.